Evaluation of antimicrobial use in the basic health units of Ponte Nova / MG - Lima, Marcelo de Paula; Batista, Rodrigo Siqueira; Moreira, Tiago Ricardo; Gomes, Andréia Patrícia (Ciência e Natura, 2022)
Antimicrobials are prescribed drugs in large quantity in Primary Care. The use of these has been highlighted in the policies to rationalize the use of medicines, for being more consumed and because these are drugs most wrongly and abusively used. The study das as an objective to evaluate the process of antibacterial therapy in primary health care of Ponte Nova/MG, identifying the classes of most used antimicrobials, the main bacterial infections, comparing them to the indications to antibacterial therapy protocols. Field research was carried out in the Basic Health Units and in the Pharmacy of Minas, based on interviews guided by a survey, structured in a database with all the information collected through the program Epiinfo 7.2.1.0. Amoxicillin was the antimicrobial that appeared the most in the prescriptions, followed by cephalexin, ciprofloxacin and azithromycin. Among the most identified infections are the urinary tract and upper respiratory tract. Brazil and the European countries presented the same antimicrobial consumption pattern. The study illustrated the major problem currently presented, the considered increased risk of bacterial resistance, as it confirmed the abusive use of antimicrobials to treat infections.